2022
DOI: 10.3389/fonc.2022.910117
|View full text |Cite
|
Sign up to set email alerts
|

Genomic landscape of lung cancer in the young

Abstract: BackgroundLung cancer in the young is a rare entity of great interest due to the high frequency of targetable mutations. In this study, we explored the genomic landscape of non-small cell lung cancer (NSCLC) in young patients and compared it with genetic alterations in older patients.MethodsComparative study of the genomic profile of NSCLC young (≤40 years old) vs older patients (>40 years old) from Instituto Nacional de Enfermedades Neoplásicas (INEN) in Lima, Peru. Archival paraffin-embedded tumor sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 26 publications
8
16
0
Order By: Relevance
“…Specific, clinically significant alterations with an associated FDA-approved targeted therapy were detected as enriched in younger patient tumors including two EGFR deletions, E746-A750 and L747-E749, and an ALK fusion, EML4-ALK. These observations align with a growing body of research conducted across various geographical regions worldwide (3,6,7,(9)(10)(11)(12)(13). We showed that younger patient tumors had significantly lower prevalence of certain genomic alterations including KRAS SNVs and MET exon 14 skipping mutations, which have previously been reported to be associated with older age (3,13,43).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Specific, clinically significant alterations with an associated FDA-approved targeted therapy were detected as enriched in younger patient tumors including two EGFR deletions, E746-A750 and L747-E749, and an ALK fusion, EML4-ALK. These observations align with a growing body of research conducted across various geographical regions worldwide (3,6,7,(9)(10)(11)(12)(13). We showed that younger patient tumors had significantly lower prevalence of certain genomic alterations including KRAS SNVs and MET exon 14 skipping mutations, which have previously been reported to be associated with older age (3,13,43).…”
Section: Discussionsupporting
confidence: 89%
“…One strength of our study is the novel way in which we defined the younger patients with NSCLC. Most age-related NSCLC studies to date use an analysis approach where a single age cutoff is selected (typically 40 to 50 years) to classify younger patients, and then compared that singularly defined group against older patients (3,6,7,(9)(10)(11)(12)(13). This analytical approach poses inherent biases based on the age threshold chosen to define younger and older patients as shown by the various age thresholds at which an association was detected in the current study (Table 2, column "Oldest age group first detected for").…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations